Albumin-related nutritional indices and all-cause and cause-specific mortality in older adults with severe dysphagia receiving artificial feeding - Wang, Jia; Pan, Wenxiu (Frontiers in Nutrition, 2026)
BackgroundOlder adults with severe dysphagia who rely on long-term enteral nutrition face high mortality risk, yet the predictive value of albumin-related nutritional markers—including the C-reactive protein–albumin–lymphocyte (CALLY) score, prognostic nutritional index (PNI), controlling nutritional status (CONUT), C-reactive protein/albumin ratio (CAR), and lymphocyte–albumin (LA)—for all-cause and infection-specific death remains unclear. In addition, direct head-to-head comparisons of these indices' prognostic performance are limited.ObjectiveTo assess whether albumin-related indices—CALLY, PNI, CONUT, CAR, and LA—are independently associated with overall and infection-specific (sepsis or pneumonia) mortality in older adults with severe dysphagia receiving long-term artificial nutrition.MethodsIn this cohort, we analyzed 236 hospitalized older Japanese patients with severe dysphagia receiving long-term artificial feeding. Associations of CALLY, PNI, CONUT, CAR, and LA with all-cause and infection-related (sepsis or pneumonia) mortality were evaluated using multivariable Cox proportional hazards models, restricted cubic spline analyses and Kaplan–Meier survival curves. Discriminative and incremental predictive performance were assessed by receiver operating characteristic (ROC) curves, net reclassification improvement (NRI) and integrated discrimination improvement (IDI). A mediation analysis tested whether hemoglobin concentration explained the observed associations, and subgroup, sensitivity and competing-risk analyses were performed to verify result robustness.ResultsHigher CALLY, PNI, and LA were independently associated with lower risks of overall and infection-related (sepsis or pneumonia) mortality, whereas higher CONUT scores predicted increased risk. CAR was related to all-cause mortality but showed no significant link with infection-specific death. Restricted cubic spline analyses revealed non-linear dose–response relationships for LA with all-cause mortality and for CONUT with sepsis/pneumonia mortality, while most other associations were approximately linear. The association between LA and sepsis/pneumonia mortality remained significant after competing-risk adjustment. ROC analyses indicated that PNI, CONUT and LA provided incremental discriminatory value compared with albumin alone. Mediation analysis suggested that hemoglobin concentration partially mediated the relationships of CALLY, CAR, and LA with all-cause mortality.ConclusionsPNI, CONUT, and LA provide incremental prognostic value beyond serum albumin for predicting all-cause mortality. In Japanese elderly patients with severe dysphagia receiving long-term enteral nutrition, LA appears particularly sensitive for identifying infection-related deaths, including sepsis and pneumonia.